Effective microorganism – X attenuates circulating superoxide dismutase following an acute bout of intermittent running in hot, humid conditions. Issue 2 (2nd April 2016) - Taylor, Lee; Lee, Ben J.; Gibson, Oliver R.; Midgley, Adrian W.; Watt, Peter; Mauger, Alexis; Castle, Paul
Abstract : This study determined the effectiveness of antioxidant supplementation on high-intensity exercise-heat stress. Six males completed a high-intensity running protocol twice in temperate conditions (TEMP; 20.4°C), and twice in hot conditions (HOT; 34.7°C). Trials were completed following7 days supplementation with 70 ml·day −1 effective microorganism-X (EM-X; TEMPEMX or HOTEMX ) or placebo (TEMPPLA or HOTPLA ). Plasma extracellular Hsp72 (eHsp72) and superoxide dismutase (SOD) were measured by ELISA. eHsp72 and SOD increased pre-post exercise (p < 0.001), with greater eHsp72 (p < 0.001) increases observed in HOT (+1.5 ng·ml −1 ) compared to TEMP (+0.8 ng·ml −1 ). EM-X did not influence eHsp72 (p > 0.05). Greater (p < 0.001) SOD increases were observed in HOT (+0.22 U·ml −1 ) versus TEMP (+0.10 U·ml −1 ) with SOD reduced in HOTEMX versus HOTPLA (p = 0.001). Physiological and perceptual responses were all greater (p < 0.001) in HOT versus TEMP conditions, with no difference followed EM-X (p > 0.05). EM-X supplementation attenuated the SOD increases following HOT, potentiating its application as an ergogenic aid to ameliorate oxidative stress.